The Nexus of Violent Victimization, Mental Health, and Employment: Findings From a Sample of Post-Incarcerated Individuals. Issue 9 (May 2023) - Liu, Lin; Lazazzara, Gabriella; Meldrum, Ryan Charles
The goals of this study were to assess the prevalence of victimization among people who are transitioning from prison to the community, and to examine the nexus of violent victimization during reentry, mental health, and weekly work hours. The participants ( n = 724; average age = 29.09 years) were interviewed before release, and in the 3rd, 9th, and 15th months into reentry. Longitudinal data about their mental health, work hours, family environment, and victimization were collected. We drew on Agnew's general strain theory and employed multilevel longitudinal modeling to examine how victimization affected respondents' work hours via mental health. Findings revealed that greater exposure to violent victimization deteriorated mental health among respondents. Furthermore, an indirect effect between victimization and reduced work capacity operating through poor mental health was observed at the between-person level. These results underscored the alarmingly high prevalence of victimization among reentering individuals and that maintaining stable employment, a critical step of reintegration after imprisonment, is difficult for reentering individuals when they become a victim of violence and suffer mental health deterioration. Implications for addressing victimization among people transitioning out of prison are discussed.